Bibliometric Analysis on The Outcomes of Teacher Leadership for Schools’ Sustainable Improvement - Bhayangkara, Athalla Nauval; Maisyaroh, Maisyaroh (Universitas Negeri Malang, 2024)
Teacher leadership is a special role and responsibility carried out by teachers so that they effectively provide services to student learning and collaborate in quality improvement towards continuous improvement of existing systems in schools. Currently, there have been many studies related to teacher leadership and of course with various research plans in the future. The purpose of this study is to find out how the outcomes of teacher leadership in sustainable school improvement by conducting an articles review supported by bibliometric analysis consisting of 78 published articles in the last decade years, from 2013 to 2023 sourced from various trusted database publishers such as Google Scholar, Science Direct, Springer, Emerald, Eric, and Proquest. The results show that the outcomes of the implementation of teacher leadership are student learning with the existence of effective learning practices by teachers in and out of the classroom supported by the existence of a supportive professional learning community and/or organizational learning environment in schools which ultimately has implications for instructional practice.